Anxiety about digital security and terrorism, and support for counter-terror measures. Issue 3 (9th July 2018) - Gallova, Viktoria; Palasinski, Marek; Shortland, Neil; Humann, Michael; Grieve, Lorraine Bowman
Abstract : Purpose: The purpose of this paper is to determine the potential predictors of anxiety about digital security, terrorist threats and support for high-tech counter measures. Design/methodology/approach: In Study 1, 195 participants indicated their anxiety about digital security systems, data protection and social networking sites. In Study 2, 107 participants indicated their anxiety about domestic terrorism, international terrorism and extremist groups. In Study 3, 261 participants indicated their support for high-tech counter-terrorism measures. Findings: Study 1 suggests that whereas anxiety about digital security systems, data protection and social networking sites was positively predicted by right-wing authoritarianism, anxiety about social networking was also negatively predicted by time spent online. Study 2 shows that time spent online was a negative predictor of anxiety about domestic terrorism. Study 3 indicates that the strongest positive predictor of support for all the measures was right-wing authoritarianism, followed by national identity. Research limitations/implications: The findings show the relevance of terror management theory to digital security and counter-terrorism. Practical implications: It appears that right-wing authoritarianism and national identity may serve as mechanisms for people to subjectively counter the presented threats. This notion may inform relevant policy and practice aimed at making communities safer and potentially helps introduce counter-terror measures with less public backlash. Social implications: When designing counter-terror measures, policy makers should consider compound national identities (e.g. Catalan or Basque people). Originality/value: The paper makes contribution to under-explored areas of terrorism anxiety and support for counter-terror measures.